A efetivação das sentenças da corte interamericana de direitos humanos no Brasil - Sales, Giorgi Augustus Nogueira Peixe (2013)
In the few decades of its recent development the International Human Rights Law achieved a satisfactory standard of regulation. Though, the human rights treaties still lack proper implementation and the correspondent bodies face difficulties in enforcing its decisions. The Inter-American System of Human Rights, created within the framework of the Organization of American States, also faces this issue. This thesis seeks to examine the legal and factual issues that may pose an obstacle to the implementation of the judgments of the Inter-American Court of Human Rights in Brazilian domestic law. It was analyzed possible instruments of enforcement under the Brazilian Constitution, legislation and courts practice in order to achieve the implementation of those judgments. The research was based on books and articles about International Human Rights Law and Constitutional Law, human rights treaties of the Inter-American Human Rights System, as well as on the analysis of the degree of compliance with rulings issued by the Inter-American Court of Human Rights against Brazil. Certain legal matters, as the possible negative effects of international rulings against third parties can pose barriers to due compliance with those decisions. Understanding the nature of the jurisdiction of international courts of human rights is one of the ways of resolving the problem. Several elements of the Brazilian legal system can be used to ensure compliance with the judgments of the Inter-American Court, regardless of a specific local legislation. It is imperative to hold a dialogue between international and national courts in order to avoid tensions between the two legal systems.